Творческое ассимилирование мифологического текста как создание трагического начала (на материале повести „Белый парoход” Ч. Айтматова) - Kaźmierczak, Natalia (Studia Rossica Posnaniensia, 2015)
This article is devoted to studying the artistic assimilation of mythological images, motifs and themes in the process of creating tragedy in The White Steamboat by Chinghiz Aitmatov. The status of the modern vision of tragedy is analyzed from the perspective of the concept of mythological thinking. The author of this article comes to the conclusion that this methodology can be applied in studying the mythologems of fate in Aitmatov's prose.